Perbandingan Kinerja Saham Syariah di Bursa Efek Indonesia dan Bursa Malaysia - Hisbullah Basri; Veny Mayasari (Universitas Indo Global Mandiri)
ABSTRACTThis research aims to determine the difference in Sharia stock performance in the Indonesia Stock Exchange and Bursa Malaysia. The population in the study is all sharia stocks listed on the Indonesia Stock Exchange and Bursa Malaysia amounting to 1,280 Sharia shares. The retrieval technique uses purposive sampling where the samples are taken with certain criteria. Meanwhile, the research sample amounted to 60 Sharia shares in which 30 sharia stocks are found on the Indonesia Stock Exchange and 30 Sharia shares in Bursa Malaysia. The research uses four indicators to use the stock performance of Return shares, Price Earning Ratio (PER), Price to Book Value (PBV), and Earning per Share (EPS). The data analysis method used in this study is quantitative analysis. The data used is secondary data, time series, and cross-section. The data analysis technique used is by conducting independent sample T-Test. The results showed that there was no difference in the performance of sharia stocks on the Indonesia Stock Exchange and Bursa Malaysia given price to book Value (PBV) and Price Earning Ratio (PER) with significance values of 0.308 and 0.264 respectively. As for the performance of shares with indicators return and EPS obtained the result that there is a difference in the performance of sharia stocks on the Indonesian stock exchange with significance values of 0.006 and 0.000 respectively. This difference is more due to the risk difference in Indonesia and Malaysia.Key words : Stock Performance, Return, EPS, PBV, PERABSTRAKPenelitian ini bertujuan untuk mengetahui perbedaan kinerja saham syariah di Bursa Efek Indonesia dan Bursa Malaysia. Populasi pada penelitian adalah seluruh saham syariah yang terdaftar di Bursa Efek Indonesia dan Bursa Malaysia yang berjumlah 1.280 saham syariah. Teknik pengambilan menggunakan purposive sampling dimana sampel diambil dengan kriteria tertentu. Sedangkan sampel penelitian ini berjumlah 60 saham syariah dimana 30 saham syariah yang terdapat di Bursa Efek Indonesia dan 30 saham syariah yang terdapat di Bursa Malaysia. Penelitian ini menggunakan empat indikator untuk menggukur kinerja saham yaitu Return Saham, Price Earning Ratio (PER), Price to Book Value (PBV), dan Earning per Share (EPS). Metode Analisis data yang digunakan dalam penelitian ini adalah analisis kuantitatif. Data yang digunakan adalah data sekunder, time series dan cross section. Teknik analisis data yang digunakan yaitu dengan melakukan independent sampel t-test. Hasil penelitian menunjukkan bahwa tidak terdapat perbedaan kinerja saham syariah di Bursa Efek Indonesia dan Bursa Malaysia di lihat dari price to book Value (PBV) dan Price Earning Ratio (PER) dengan nilai signifikansi masing-masing sebesar 0,308 dan 0,264. Sedangkan untuk kinerja saham dengan indikator return dan EPS didapat hasil bahwa terdapat perbedaan kinerja saham syariah di Bursa Efek Indonesia dengan nilai signifikansi masing-masing sebesar 0,006 dan 0,000.Kata kunci: Kinerja Saham, Return, EPS, PBV, PER